Life, Liberty, and the Pursuit of Happiness: Ten Years of the Claremont Review of Books - Kesler, Charles R.; Kienker, John B. (Rowman & Littlefield Publishers, 2012)
Over the past 10 years, the Claremont Review of Books has become one of the preeminent conservative magazines in the United States, offering bold arguments for a reinvigorated conservatism that draws upon the timeless principles of the American Founding and applies them to the moral and political problems we face today. With essays by the likes of William F. Buckley, Jr., Christopher Hitchens, Richard Brookheiser, James Q. Wilson, Allen C. Guelzo, Victor Davis Hanson, Ross Douthat, and many others, this collection surveys the range of issues addressed in the Claremont Review of Books first decade, from the conservative critique of American progressivism to foreign policy, politics, history, and culture. Liberally illustrated with art director Elliot Banfield's popular cartoons, Life, Liberty, and the Pursuit of Happiness provides the magazine's many devotees with a treasured keepsake of a tumultuous decade and will be of interest to all those who care about American politics and culture. Among the contributors are Hadley Arkes, Martha Bayles, the late William F. Buckley, Jr., Paul Cantor, James Ceaser, Joseph Epstein, Christopher Flannery, Harvey Mansfield, Wilfred McClay, Cheryl Miller, the late Jaroslav Pelikan, Joseph Tartakovsky, Michael Uhlmann, Algis Valiunas, William Voegeli, and the late James Q. Wilson.